Late Luteal Hyperprolactinemia (LL-HPRL) is not a disease..!!! - Allow, Ahmed Kaid Naji; Abdulmogny, A. Sadek S.M.; Maryam, Bracamonte; Ahmed Kaid, Belqees (Medwell Journals, 2015)
Prolactin (PRL) is an exceptional hormone of pituitary gland with important implications for normal reproduction as well as for sexual behavior. It increases in the first trimester of pregnancy (physiological hyperprolactinemia). The objective of this study is to evaluate the usefulness of LL-HPRL as an indicator for early ongoing pregnancy in patients undergoing treatment for infertility. This is a retrospective study on one hundred and eleven women who had beenundergoing treatment for infertilityand their husbands were known to be reproductively fertile. Women with knownother causesof infertility, besides anovulation and luteal phase deficiency were excluded from the study population. They were divided into two groups matched for age and Body-Mass Index (BMI); control group A: 76 pregnant women on no anti-LF-HPRL therapy and study group B: 35 pregnant women on anti-LF-HPRL therapy. All women in both groups had been treated for hyperprolactinemia until their PRL levels were normal. Later, after one menstrual cycle, both groups had been enrolled in a Controlled Ovarian hyperstimulation (COS) Program. The COS aimed to induce 2-3 mature follicles/women/cycle. Duringthe study period (34 months), the ovulation, pregnancy, abortion and live-birth rates were evaluated. The withdrawal rate of patients was also recorded. No significant differences were observed between the two groups of women regarding baseline hormonal levels (FSH, LH, LH/FSH, testosterone, estradiol and PRL (p<0.03). However, the progesterone levels at day 21 of the cycle was significantly different between study and control groups (4.52±4.91 and 5.36±4.73, respectively, p<0.02). The serum PRL at 28th day of ovulation induction cycle was significantly different between the study and control groups (28.32±11.89 and 7.53±5.69, respectively, p<0.001). The ovulation, ongoing pregnancy, life-birth rates were significantly higher in the study group in comparison to control group (p<0.001). Early abortion and cancelation rates were significantly higher in control than in study group (p<0.001). High serum prolactin levels in the Late Follicular menstrual Phase (LF-HPRL) in infertile women treated by ovulation induction after having completed therapy for hyperprolactinemia is an early indicator for diagnosis of ongoing pregnancy, consequently treatment of LF-HPRL is not recommended.